Investigation on the Corrosion of Coated Steel Plates with Impact Defect using Divided Steel Plates - Marish S. Madlangbayan; Nobuaki Otsuki; Takahiro Nishida; Tsuyoshi Saito (Salehan Institute of Higher Education, 2018)
A method utilizing divided steel plates was used to investigate the corrosion of coated steel plates with impact defect while continuously submerged in 3% NaCl solution. The polarization behavior of circular divided steel plates was first compared to that of undivided ones. Half-cell potential and polarization resistance results show similar trend in divided and undivided form especially at the later stages of exposure. The method of using circular divided steel plates was then used to monitor the macrocell as well as microcell corrosion in coated steel plates induced with defect. The test results show that the defect causes macrocell corrosion to occur between the defect and sound portions. The impact defect also caused the reduction in the polarization resistance and consequently higher microcell corrosion at the neighbouring sound coated portions.